Norma, Identitas, dan Kepentingan: Bingkai Konstruktivisme atas Keanggotaan Indonesia di BRICS - Ananggadipa Kintoko; Asra Virgianita (Jurnal Sentris, 2026)
The emergence of a multipolar trading system has prompted developing countries, including Indonesia, to recalibrate their foreign policy strategies and orientations. This study examines the motives influencing Indonesia’s policies and strategies in its BRICS membership through a constructivist perspective and the concept of national interest. The findings reveal that Indonesia’s decision to join BRICS was driven not only by economic considerations but also by social constructs encompassing national identity, international norms, and the reconstruction of interests. Indonesia’s identity as a middle power, guided by the principle of a free and active foreign policy, underpins its stance on BRICS membership. Furthermore, the internalisation of BRICS norms into national policy has encouraged a shift in Indonesia’s diplomacy from a predominantly material-oriented approach to one that extends into the normative sphere. The interaction between identity and norms has shaped national interests that affirm Indonesia’s role as a normative middle power and as a bridge between the Global South and the Global North. Thus, Indonesia’s membership in BRICS illustrates a process of identity interaction and adaptation that reinforces its position as an active actor within the grouping.